Membrane electrode, preparation method thereof and monocell

By adopting a dual cathode catalytic layer design in a proton exchange membrane fuel cell, the equilibrium performance and durability of the cathode side of the cathode side is used to solve the problem of large mass transfer resistance of the cathode catalytic layer in the prior art, and the membrane electrode performance improvement and durability improvement are achieved.

CN119560597APending Publication Date: 2025-03-04FTXT ENERGY TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311060827.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the existing proton exchange membrane fuel cells, there is a large mass transfer resistance in the oxygen reduction kinetic process of the cathode catalytic layer, which leads to limited battery performance and difficulty in taking into account both performance and durability.

Method used

Using a dual cathode catalytic layer design, the particle size D50 of platinum in the first catalytic layer is < the particle size D50 of platinum in the second catalytic layer. By setting ink slurry of different formulations on the cathode side, the performance and durability are balanced, and the material utilization and overall durability are improved.

Benefits of technology

It has achieved improvements in membrane electrode performance and improvements in overall durability, maximized the use of materials, reduced costs, and has good development potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560597A_ABST
    Figure CN119560597A_ABST
Patent Text Reader

Abstract

The invention provides a membrane electrode, a preparation method thereof and a monocell, the membrane electrode comprises a double-cathode catalyst layer, a proton exchange membrane and a gas diffusion layer, the double-cathode catalyst layer comprises a first catalyst layer and a second catalyst layer; the first catalyst layer is connected with the proton exchange membrane, and the second catalyst layer is connected with the gas diffusion layer; the raw materials of the double-cathode catalyst layer comprise a platinum-containing catalyst and an ionomer; the particle size D50 of platinum in the first catalyst layer is smaller than the particle size D50 of platinum in the second catalyst layer. The double-cathode catalyst layer is arranged, and the particle size D50 of platinum in the first catalyst layer is smaller than the particle size D50 of platinum in the second catalyst layer, so that the utilization rate of the material is improved to the maximum extent, the cost is reduced, the performance and the overall durability of the membrane electrode are improved, and the membrane electrode has good development potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fuel cells, and in particular relates to a membrane electrode and a preparation method thereof and a single cell. Background Art

[0002] Proton exchange membrane fuel cells have outstanding advantages such as high energy density, high energy conversion efficiency, low start-up temperature and low pollution. They are an effective conversion device with broad application prospects. However, in order to successfully achieve commercialization, technologies to reduce costs, increase power density and improve durability must be developed, which is the main obstacle to the widespread application of proton exchange membrane fuel cells. The electrochemical reaction generally occurs at the junction of the catalyst layer and the proton exchange membrane of the membrane electrode assembly. The core component of the proton exchange membrane fuel cell is the membrane electrode assembly, which is composed of a proton exchange membrane, an anode and cathode catalyst layer and a gas diffusion layer stacked together. The catalyst layer, as the place where the electrochemical reaction occurs, is a key component of the membrane electrode. The electrode catalyst layer is composed of three phases, namely, an ionic polymer phase that conducts protons, a Pt / C catalyst phase that conducts electrons, and a pore phase that transfers gas. Electrochemical reactions can only occur in the intersection area (three-phase region) of electron, proton and gas pathways, so the composition of each phase of the catalyst layer and the transmission of each component therein have a great influence on the electrode reaction. Although the research of proton exchange membrane fuel cells has made many significant progress, large voltage loss is still inevitable, which is mainly due to the large mass transfer resistance caused by the slow oxygen reduction kinetics in the cathode catalyst layer. Therefore, in a proton exchange membrane fuel cell, the characteristics of the cathode catalyst layer have a very important influence on the performance of the entire cell.

[0003] The catalyst layer of the membrane electrode is mainly composed of Pt / C catalyst and Nafion ionomer. The current design concept of the conventional membrane electrode catalyst layer structure is to coat a formula of ink slurry (pore structure and material composition) on the proton exchange membrane and evenly distribute it in the single cell. However, the operation of the fuel cell is a very complicated process. The internal reaction state near the proton exchange membrane is different from the reaction state near the gas diffusion layer. Figure 1As shown in the figure, the longitudinal transmission paths of gas, protons and electrons in the catalyst coating membrane affect the reaction state successively. Although at the interface between the catalyst layer and the membrane, a high content of Nafion is conducive to proton migration, and a high loading of Pt / C catalyst is conducive to high efficiency of oxygen reduction electrochemical reaction, a high content of Nafion near the gas diffusion layer is prone to flooding, which increases the gas diffusion resistance and thus hinders the improvement of membrane electrode performance, especially at high current density. In addition, the high loading of Pt / C catalyst on the side close to the gas diffusion layer greatly reduces the utilization rate of the platinum catalyst in the entire membrane electrode. It is crucial to ensure the utilization rate of platinum for high-performance and high-durability membrane electrodes. Whether it is water shortage or flooding of the proton exchange membrane, the battery performance will be reduced, which will seriously affect its durability.

[0004] In order to design the best cathode and anode catalyst layer structure, the traditional method is to change the catalyst type, catalyst amount, ionomer type or ionomer content of each cathode and anode to configure a formula to evenly coat the proton exchange membrane, and then assemble it into a battery to carry out fuel cell performance evaluation and durability test under operating conditions. Finally, based on the results obtained, the best cathode and anode catalyst layers that can maximize the performance and durability of the designed fuel cell are selected.

[0005] However, the conventional approach does not take into account that the reaction state of the catalyst layer on the side close to the proton exchange membrane is different from the reaction state on the side close to the gas diffusion layer, so the developed membrane electrode cannot take into account both performance and durability.

[0006] Therefore, how to simultaneously take into account the high performance and durability of membrane electrodes is a difficult point that urgently needs to be studied.

[0007] In order to solve this problem, this paper invented a new dual-catalytic layer design method. Specifically, two ink slurries with different formulas are prepared on the cathode side to balance the relationship between performance and durability, maximize material utilization and reduce product costs. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a membrane electrode and a preparation method thereof and a single cell. The present invention not only maximizes the utilization rate of materials and reduces costs by setting a double cathode catalyst layer, but also improves the performance and overall durability of the membrane electrode, and has good development potential.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a membrane electrode, the membrane electrode comprising a dual cathode catalyst layer, a proton exchange membrane and a gas diffusion layer, the dual cathode catalyst layer comprising a first catalyst layer and a second catalyst layer;

[0011] The first catalytic layer is connected to the proton exchange membrane, and the second catalytic layer is connected to the gas diffusion layer;

[0012] The raw materials of the dual cathode catalyst layer include a platinum-containing catalyst and an ionomer;

[0013] The particle size D50 of platinum in the first catalytic layer is less than the particle size D50 of platinum in the second catalytic layer.

[0014] The present invention provides a double cathode catalyst layer, and the particle size D50 of platinum in the first catalyst layer is less than the particle size D50 of platinum in the second catalyst layer, which not only maximizes the utilization rate of materials and reduces costs, but also improves the performance and overall durability of the membrane electrode, and has good development potential.

[0015] It should be noted that the gas diffusion layer includes an anode gas diffusion layer and a cathode gas diffusion layer, and the second catalyst layer is connected to the cathode gas diffusion layer.

[0016] Preferably, the membrane electrode further includes an anode catalyst layer.

[0017] It should be noted that an "ideal" catalyst layer structure should be able to maximize the use of catalytic active centers while minimizing mass transfer resistance. The oxygen concentration is highest near the gas diffusion layer. As oxygen is transported toward the proton exchange membrane, the concentration gradually decreases, while the proton concentration changes in the opposite direction. The closer to the gas diffusion layer, the lower the proton concentration. From the perspective of proton supply, more platinum in the catalyst layer should be distributed near the proton exchange membrane, while the amount of platinum can be reduced and the porosity can be increased near the gas diffusion layer to promote gas transmission and electrode drainage. The ideal platinum distribution should comprehensively consider the distribution of proton concentration and oxygen concentration, that is, the most distributed at a certain position in the middle of the catalyst layer. This area is the best balance point between proton concentration and oxygen diffusion concentration.

[0018] In addition, from the durability point of view, the water generated by the fuel cell during actual operation will be discharged toward the gas diffusion layer, so the water content of the catalyst layer near the gas diffusion layer (or the interface between the catalyst layer and the gas diffusion layer) is higher than that near the membrane. This is why the thinning of the catalyst layer occurs in the catalyst layer near the gas diffusion layer, such as Figure 2 shown.

[0019] Therefore, in order to balance the performance and durability of the electrode surface close to the proton membrane and the side close to the gas diffusion layer, the present invention uses different catalyst layer structures on the electrode side close to the proton membrane and the side close to the gas diffusion layer. Specifically, the first catalyst layer close to the proton membrane is used to improve performance, and the second catalyst layer close to the gas diffusion layer is used to improve durability, and the particle size D50 of platinum in the first catalyst layer is less than the particle size D50 of platinum in the second catalyst layer. Through the above design, not only can the material be used to the maximum extent and the cost can be reduced, but also the purpose of improving the performance and durability of the membrane electrode can be taken into account at the same time.

[0020] In the present invention, the particle size D50 of platinum in the first catalytic layer is less than the particle size D50 of platinum in the second catalytic layer, which can improve the activity and durability of the catalyst, because the smaller the particle size, the larger the specific surface area and the greater the mass activity. The larger the particle size, the more compact the platinum nanoparticles, the slower the dissolution and the better the stability.

[0021] It should be noted that the platinum-containing catalyst in the first catalytic layer and the platinum-containing catalyst in the second catalytic layer are platinum-containing catalysts of different types.

[0022] As a preferred technical solution of the present invention, the particle size D50 of platinum in the first catalytic layer is 1-3 nm, for example, it can be 1 nm, 1.5 nm, 2 nm, 2.5 nm or 3 nm, etc., preferably 2.2-2.6 nm.

[0023] Preferably, the particle size D50 of platinum in the second catalytic layer is 4-6 nm, for example, 4 nm, 4.5 nm, 5 nm, 5.5 nm or 6 nm, etc., preferably 5.2-5.6 nm.

[0024] Preferably, the pores of the first catalytic layer are smaller than the pores of the second catalytic layer.

[0025] In the present invention, the pores of the first catalytic layer are smaller than the pores of the second catalytic layer, which can ensure the smooth transmission of oxygen, reduce the mass transfer overpotential, and improve the high current density performance.

[0026] Preferably, the porosity of the first catalytic layer is 20%-30%, for example, it may be 20%, 22%, 24%, 25.4%, 27%, 28% or 30%.

[0027] Preferably, the porosity of the second catalytic layer is 35%-45%, for example, 35%, 37%, 38%, 38.5%, 40%, 42% or 45%.

[0028] As a preferred technical solution of the present invention, the platinum loading of the first catalytic layer is greater than the platinum loading of the second catalytic layer.

[0029] In the present invention, by limiting the platinum loading of the first catalytic layer to be greater than the platinum loading of the second catalytic layer, the active sites of the first catalytic layer can be increased to accelerate the electrochemical reaction rate, improve membrane electrode performance, increase platinum utilization, and reduce costs.

[0030] Preferably, the platinum loading of the first catalytic layer is 0.2-0.3 mg / cm 2 , for example, it can be 0.2 mg / cm 2 , 0.22mg / cm 2 , 0.24mg / cm 2 , 0.26mg / cm 2 、0.28mg / cm 2 or 0.3mg / cm 2 etc., preferably 0.22-0.26 mg / cm 2 .

[0031] In the present invention, if the platinum loading of the first catalytic layer is too little, the protons transferred from the anode cannot react electrochemically with oxygen at sufficient active sites, affecting the membrane electrode performance; if the platinum loading of the first catalytic layer is too much, the active sites are oversaturated, the membrane electrode performance cannot be further improved, and materials will be wasted and product costs will be increased.

[0032] Preferably, the platinum loading of the second catalytic layer is 0.05-0.1 mg / cm 2 , for example, it can be 0.05 mg / cm 2 , 0.06mg / cm 2 , 0.07mg / cm 2 , 0.08mg / cm 2 , 0.09mg / cm 2 or 0.1mg / cm 2 etc., preferably 0.06-0.07 mg / cm 2 .

[0033] In the present invention, if the platinum loading of the second catalytic layer is too little, the protons transferred from the anode cannot react electrochemically with oxygen at sufficient active sites, affecting the membrane electrode performance; if the platinum loading of the second catalytic layer is too much, the active sites are oversaturated, the membrane electrode performance cannot be further improved, and materials will be wasted to increase product costs.

[0034] As a preferred technical solution of the present invention, the platinum-containing catalyst includes a platinum-carbon catalyst.

[0035] Preferably, in the platinum-carbon catalyst, based on the mass content of carbon, the mass content of platinum in the first catalytic layer is greater than the mass content of platinum in the second catalytic layer.

[0036] In the present invention, by limiting the mass content of platinum in the first catalytic layer to be greater than the mass content of platinum in the second catalytic layer, the first catalytic layer can more easily accelerate the reaction rate of oxygen reduction, the structure of the second catalytic layer can be more stable, and the utilization rate of platinum can be improved, thereby reducing costs and improving durability.

[0037] Preferably, based on the mass content of carbon, the mass content of platinum in the first catalytic layer is 40-60%, for example, 40%, 45%, 50%, 55% or 60%, etc., preferably 45-55%.

[0038] Preferably, based on the mass content of carbon, the mass content of platinum in the second catalytic layer is 19-30%, for example, 19%, 22%, 24%, 26%, 28% or 30%, etc., preferably 19.4%.

[0039] Preferably, the specific surface area of ​​the carbon carrier in the first catalytic layer is greater than the specific surface area of ​​the carbon carrier in the second catalytic layer.

[0040] In the present invention, by limiting the specific surface area of ​​the carbon carrier in the first catalytic layer to be greater than the specific surface area of ​​the carbon carrier in the second catalytic layer, the platinum in the first catalytic layer can be more easily dispersed evenly on the surface of the carbon carrier, thereby accelerating the reaction rate of oxygen reduction (ORR) and improving the utilization rate of platinum. The second catalytic layer is more conducive to mass transfer, has good crystallinity and good stability.

[0041] Preferably, the specific surface area of ​​the carbon carrier in the first catalytic layer is 800-1000m 2 / g, for example, it can be 800m 2 / g, 850m 2 / g、900m 2 / g, 950m 2 / g or 1000m 2 / g, etc., preferably 860-900m 2 / g.

[0042] Preferably, the specific surface area of ​​the carbon carrier in the second catalytic layer is 50-300 m 2 / g, for example, it can be 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g or 300m 2 / g, etc., preferably 120-200m 2 / g.

[0043] As a preferred technical solution of the present invention, the ionomer includes any one of fluorinated sulfonic acid polymer Nafion, ethanol, water or n-propanol, or a combination of at least two thereof.

[0044] Preferably, the I / C ratio in the first catalytic layer is greater than the I / C ratio in the second catalytic layer.

[0045] In the present invention, by limiting the I / C ratio in the first catalytic layer to be greater than the I / C ratio in the second catalytic layer, the first catalytic layer can more easily form a continuous proton transfer network, thereby accelerating the ORR reaction rate, and the second catalytic layer is more conducive to mass transfer.

[0046] Preferably, the I / C ratio in the first catalytic layer is 0.6-1.2, for example, it can be 0.6, 0.7, 0.8, 0.9, 1, 1.1 or 1.2, etc., preferably 1.1-1.15.

[0047] In the present invention, if the I / C ratio in the first catalytic layer is too small, the proton conduction resistance will increase, affecting proton conduction; if the I / C ratio in the first catalytic layer is too large, the catalytic layer is easily flooded, affecting gas transmission.

[0048] Preferably, the I / C ratio in the second catalytic layer is 0.1-0.5, for example, it can be 0.1, 0.2, 0.3, 0.4 or 0.5, etc., preferably 0.3-0.4.

[0049] In the present invention, if the I / C ratio in the second catalytic layer is too small, the proton conduction resistance will increase, affecting proton conduction; if the I / C ratio in the second catalytic layer is too large, the catalytic layer is easily flooded, affecting gas transmission.

[0050] As a preferred technical solution of the present invention, the EW value of the ionomer in the first catalytic layer is less than the EW value of the ionomer in the second catalytic layer.

[0051] In the present invention, by limiting the EW value of the ionomer in the first catalytic layer to less than the EW value of the ionomer in the second catalytic layer, the first catalytic layer can more easily form a continuous proton transfer network, thereby accelerating the ORR reaction rate, and the second catalytic layer is more conducive to mass transfer.

[0052] It should be noted that EW refers to the weight of the polymer / the amount of SO3H groups per 1 mol.

[0053] Preferably, the EW value of the ionomer in the first catalytic layer is 700-800 g / eq, for example, it can be 700 g / eq, 720 g / eq, 740 g / eq, 760 g / eq, 780 g / eq or 800 g / eq, etc., preferably 720-740 g / eq.

[0054] Preferably, the EW value of the ionomer in the second catalytic layer is 900-1000 g / eq, for example, it can be 900 g / eq, 920 g / eq, 940 g / eq, 960 g / eq, 980 g / eq or 1000 g / eq, etc., preferably 905-920 g / eq.

[0055] In a second aspect, the present invention provides a method for preparing a membrane electrode containing a double cathode catalyst layer as described in the first aspect, the preparation method comprising the following steps:

[0056] (1) mixing a platinum-containing catalyst, an ionomer, and a solvent in a first ratio to obtain a first catalyst layer slurry; mixing a platinum-containing catalyst, an ionomer, and a solvent in a second ratio to obtain a second catalyst layer slurry;

[0057] (2) coating the second catalytic layer slurry on the substrate membrane, and drying it once to obtain the second catalytic layer; coating the first catalytic layer slurry on the second catalytic layer, and drying it twice to obtain the first catalytic layer;

[0058] (3) placing the side of the substrate membrane covered with the second catalytic layer and the first catalytic layer on one side of a proton exchange membrane, hot pressing, peeling off the substrate membrane to obtain a dual cathode catalytic layer, assembling the dual cathode catalytic layer with a gas diffusion layer to obtain the membrane electrode.

[0059] As a preferred technical solution of the present invention, in the first proportion mixing of step (1), the mass ratio of the platinum-containing catalyst, the ionomer and the solvent is (3-10):(10-20):(30-50), wherein the selection range of the platinum-containing catalyst "3-10" can be, for example, 3, 5, 7 or 10, etc., the selection range of the ionomer "10-20" can be, for example, 10, 12, 14, 16, 18 or 20, etc., and the selection range of the solvent "30-50" can be, for example, 30, 35, 40, 45 or 50, etc.

[0060] Preferably, in the second proportion mixing of step (1), the mass ratio of the platinum-containing catalyst, the ionomer and the solvent is (1-5):(5-10):(30-40), wherein the selection range of the platinum-containing catalyst "1-5" can be, for example, 1, 2, 3, 4 or 5, the selection range of the ionomer "5-10" can be, for example, 5, 6, 7, 8, 9 or 10, and the selection range of the solvent "30-40" can be, for example, 30, 32, 34, 36, 38 or 40, etc.

[0061] The present invention does not specifically limit the type of solvent. For example, it can be an alcohol solvent or water, such as n-propanol or deionized water.

[0062] Preferably, the temperature of the primary drying and the secondary drying in step (2) is independently 60-70°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C.

[0063] Preferably, in step (3), a dielectric membrane is provided on the side of the base membrane not covered with the second catalytic layer and the first catalytic layer.

[0064] It should be noted that the function of this dielectric membrane is to be used as a material for coating ink. The fluid catalyst ink is evenly coated on the base membrane, and then dried in an oven to form a solid catalyst layer. The catalyst layer on the base membrane is transferred to the proton exchange membrane through a hot pressing process to form a CCM electrode.

[0065] Preferably, the material of the base film and the dielectric film is independently any one of polytetrafluoroethylene (PTFE), polyester resin (OET) or polypropylene (PP), or a combination of at least two of them.

[0066] Preferably, the temperature of the hot pressing in step (3) is 130-160°C, for example, 130°C, 140°C, 150°C or 160°C.

[0067] Preferably, the hot pressing time in step (3) is 30-60 seconds, for example, 30 seconds, 40 seconds, 50 seconds or 60 seconds.

[0068] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0069] (1) mixing and dispersing a platinum-containing catalyst, an ionomer, and a solvent in a mass ratio of (3-10):(10-20):(30-50) to obtain a first catalyst layer slurry; mixing and dispersing a platinum-containing catalyst, an ionomer, and a solvent in a mass ratio of (1-5):(5-10):(30-40) to obtain a second catalyst layer slurry;

[0070] (2) coating the second catalytic layer slurry on the substrate membrane, and drying it once at 60-70° C. to obtain the second catalytic layer; coating the first catalytic layer slurry on the second catalytic layer, and drying it twice at 60-70° C. to obtain the first catalytic layer;

[0071] (3) placing one side of the base membrane covered with the second catalytic layer and the first catalytic layer on one side of a proton exchange membrane, and setting a dielectric membrane on the other side, and then hot pressing at 130-160° C. for 30-60 seconds, peeling off the base membrane to obtain a dual cathode catalytic layer, and assembling the dual cathode catalytic layer with a gas diffusion layer to obtain the membrane electrode.

[0072] In a third aspect, the present invention provides a single cell, comprising an anode plate, a cathode plate and the membrane electrode as described in the first aspect, wherein the anode plate and the cathode plate are respectively connected to two end surfaces of the membrane electrode.

[0073] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0074] Compared with the prior art, the present invention has the following beneficial effects:

[0075] The present invention sets a first catalytic layer on the side close to the proton membrane to improve performance, sets a second catalytic layer on the side close to the gas diffusion layer to improve durability, and the particle size D50 of platinum in the first catalytic layer is less than the particle size D50 of platinum in the second catalytic layer. Through the above design, not only can the material be used to the maximum extent and the cost be reduced, but also the purpose of improving the performance and durability of the membrane electrode can be taken into account at the same time, and it has good development potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 It is a schematic diagram of the structure and principle of the membrane electrode in the prior art.

[0077] Figure 2 This is a diagram showing the structural changes in the catalyst layer of the fuel cell after 1000 cycles of actual operation.

[0078] Figure 3 This is a schematic cross-sectional view of the membrane electrode prepared in Example 1 of the present invention.

[0079] Among them, 1-anode gas diffusion layer; 2-anode catalyst layer; 3-proton exchange membrane; 4-first catalyst layer; 5-second catalyst layer; 6-dual cathode catalyst layer; 7-cathode gas diffusion layer. DETAILED DESCRIPTION

[0080] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0081] Example 1

[0082] This embodiment provides a membrane electrode containing a double cathode catalyst layer 6, and the cross-sectional schematic diagram of the membrane electrode is as follows Figure 3As shown, the membrane electrode comprises a double cathode catalyst layer 6, a proton exchange membrane 3, a cathode gas diffusion layer 7, an anode gas diffusion layer 1 and an anode catalyst layer 2, the double cathode catalyst layer 6 comprises a first catalyst layer 4 and a second catalyst layer 5; the first catalyst layer 4 is connected to the proton exchange membrane 3, and the second catalyst layer 5 is connected to the cathode gas diffusion layer 7; the raw materials of the double cathode catalyst layer 6 include a platinum carbon catalyst and an ionomer Nafion;

[0083] The platinum loading of the first catalytic layer 4 (0.25 mg / cm 2 )>the platinum loading of the second catalytic layer 5 (0.07 mg / cm 2 );

[0084] The particle size D50 (2 nm) of platinum in the first catalytic layer 4 is less than the particle size D50 (5 nm) of platinum in the second catalytic layer 5;

[0085] The porosity of the first catalytic layer 4 (25.6%) is less than the porosity of the second catalytic layer 5 (38.7%);

[0086] The specific surface area of ​​the carbon carrier in the first catalytic layer 4 (900m 2 / g)>Specific surface area of ​​carbon support in the second catalytic layer 5 (150m 2 / g);

[0087] The I / C ratio in the first catalytic layer 4 (0.9) is greater than the I / C ratio in the second catalytic layer 5 (0.3);

[0088] The EW value of the ionomer in the first catalytic layer 4 (750 g / eq) is less than the EW value of the ionomer in the second catalytic layer 5 (950 g / eq).

[0089] This embodiment also provides a method for preparing the above membrane electrode, and the method for preparing the membrane electrode comprises the following steps:

[0090] (1) nano-mixing and dispersing a platinum-carbon catalyst (the mass fraction of platinum is 51%), ionomer Nafion and water in a mass ratio of 5:14:41 to obtain a first catalytic layer slurry; nano-mixing and dispersing a platinum-carbon catalyst (the mass fraction of platinum is 19.4%), ionomer Nafion and solvent in a mass ratio of 3:8:35 to obtain a second catalytic layer slurry, wherein the platinum-carbon catalysts in the two slurries are of different types;

[0091] (2) coating the second catalyst layer slurry on the substrate PTFE, and drying it once at 60° C. to obtain the second catalyst layer 5; coating the first catalyst layer slurry on the second catalyst layer 5, and drying it twice at 60° C. to obtain the first catalyst layer 4;

[0092] (3) The side of the base membrane covered with the second catalytic layer 5 and the first catalytic layer 4 is placed on one side of the proton exchange membrane 3, and the other side is provided with a dielectric membrane PTFE, and then hot pressing is performed at 130°C for 60 seconds to peel off the base membrane to obtain a dual cathode catalytic layer 6, and the dual cathode catalytic layer 6 is assembled with a gas diffusion layer to obtain the membrane electrode.

[0093] Example 2

[0094] This embodiment provides a membrane electrode containing a dual cathode catalyst layer 6, the membrane electrode comprising a dual cathode catalyst layer 6, a proton exchange membrane 3, a cathode gas diffusion layer 7, an anode gas diffusion layer 1 and an anode catalyst layer 2, the dual cathode catalyst layer 6 comprising a first catalyst layer 4 and a second catalyst layer 5; the first catalyst layer 4 is connected to the proton exchange membrane 3, and the second catalyst layer 5 is connected to the cathode gas diffusion layer 7; the raw materials of the dual cathode catalyst layer 6 include a platinum carbon catalyst and an ionomer Nafion;

[0095] The platinum loading of the first catalytic layer 4 (0.2 mg / cm 2 )>the platinum loading of the second catalytic layer 5 (0.05 mg / cm 2 );

[0096] The particle size D50 (1 nm) of platinum in the first catalytic layer 4 is less than the particle size D50 (4 nm) of platinum in the second catalytic layer 5;

[0097] The pores of the first catalytic layer 4 (23.6%) are less than the pores of the second catalytic layer 5 (35.5%);

[0098] The specific surface area of ​​the carbon carrier in the first catalytic layer 4 (800 m 2 / g)>Specific surface area of ​​carbon support in the second catalytic layer 5 (50m 2 / g);

[0099] The I / C ratio in the first catalytic layer 4 (0.6) is greater than the I / C ratio in the second catalytic layer 5 (0.1);

[0100] The EW value of the ionomer in the first catalytic layer 4 (700 g / eq) is less than the EW value of the ionomer in the second catalytic layer 5 (900 g / eq).

[0101] This embodiment also provides a method for preparing the above membrane electrode, and the method for preparing the membrane electrode comprises the following steps:

[0102] (1) nano-mixing and dispersing a platinum-carbon catalyst (the mass fraction of platinum is 40%), ionomer Nafion and water in a mass ratio of 3:10:30 to obtain a first catalyst layer slurry; nano-mixing and dispersing a platinum-carbon catalyst (the mass fraction of platinum is 25%), ionomer Nafion and solvent in a mass ratio of 1:5:30 to obtain a second catalyst layer slurry, wherein the platinum-carbon catalysts in the two slurries are of different types;

[0103] (2) coating the second catalyst layer slurry on the substrate PTFE, and drying it once at 60° C. to obtain the second catalyst layer 5; coating the first catalyst layer slurry on the second catalyst layer 5, and drying it twice at 60° C. to obtain the first catalyst layer 4;

[0104] (3) The side of the base membrane covered with the second catalytic layer 5 and the first catalytic layer 4 is placed on one side of the proton exchange membrane 3, and the other side is provided with a dielectric membrane PTFE, and then hot pressing is performed at 130°C for 60 seconds to peel off the base membrane to obtain a dual cathode catalytic layer 6, and the dual cathode catalytic layer 6 is assembled with a gas diffusion layer to obtain the membrane electrode.

[0105] Example 3

[0106] This embodiment provides a membrane electrode containing a dual cathode catalyst layer 6, the membrane electrode comprising a dual cathode catalyst layer 6, a proton exchange membrane 3, a cathode gas diffusion layer 7, an anode gas diffusion layer 1 and an anode catalyst layer 2, the dual cathode catalyst layer 6 comprising a first catalyst layer 4 and a second catalyst layer 5; the first catalyst layer 4 is connected to the proton exchange membrane 3, and the second catalyst layer 5 is connected to the cathode gas diffusion layer 7; the raw materials of the dual cathode catalyst layer 6 include a platinum carbon catalyst and an ionomer Nafion;

[0107] The platinum loading of the first catalytic layer 4 (0.3 mg / cm 2 )>the platinum loading of the second catalytic layer 5 (0.1 mg / cm 2 );

[0108] The particle size D50 (3 nm) of platinum in the first catalytic layer 4 is less than the particle size D50 (6 nm) of platinum in the second catalytic layer 5;

[0109] The porosity of the first catalytic layer 4 (27.4%) is less than the porosity of the second catalytic layer 5 (44.7%);

[0110] The specific surface area (1000 m 2 / g)>Specific surface area of ​​carbon support in the second catalytic layer 5 (300m 2 / g);

[0111] The I / C ratio in the first catalytic layer 4 (1.2)> the I / C ratio in the second catalytic layer 5 (0.5);

[0112] The EW value of the ionomer in the first catalytic layer 4 (800 g / eq) is less than the EW value of the ionomer in the second catalytic layer 5 (1000 g / eq).

[0113] This embodiment also provides a method for preparing the above membrane electrode, and the method for preparing the membrane electrode comprises the following steps:

[0114] (1) nano-mixing and dispersing a platinum-carbon catalyst (the mass fraction of platinum is 60%), ionomer Nafion and water in a mass ratio of 10:20:50 to obtain a first catalyst layer slurry; nano-mixing and dispersing a platinum-carbon catalyst (the mass fraction of platinum is 30%), ionomer Nafion and solvent in a mass ratio of 5:10:40 to obtain a second catalyst layer slurry, wherein the platinum-carbon catalysts in the two slurries are of different types;

[0115] (2) coating the second catalyst layer slurry on the substrate PTFE, and drying it once at 60° C. to obtain the second catalyst layer 5; coating the first catalyst layer slurry on the second catalyst layer 5, and drying it twice at 60° C. to obtain the first catalyst layer 4;

[0116] (3) The side of the base membrane covered with the second catalytic layer 5 and the first catalytic layer 4 is placed on one side of the proton exchange membrane 3, and the other side is provided with a dielectric membrane PTFE, and then hot pressing is performed at 130°C for 60 seconds to peel off the base membrane to obtain a dual cathode catalytic layer 6, and the dual cathode catalytic layer 6 is assembled with a gas diffusion layer to obtain the membrane electrode.

[0117] Example 4

[0118] The difference between this embodiment and embodiment 1 is that the coating amount of the first catalyst layer slurry is adjusted so that the platinum loading of the first catalyst layer 4 is 0.15 mg / cm 2 .

[0119] The rest of the preparation methods and parameters were the same as those in Example 1.

[0120] Example 5

[0121] The difference between this embodiment and embodiment 1 is that the coating amount of the first catalyst layer slurry is adjusted so that the platinum loading of the first catalyst layer 4 is 0.35 mg / cm 2 .

[0122] The rest of the preparation methods and parameters were the same as those in Example 1.

[0123] Example 6

[0124] The difference between this embodiment and embodiment 1 is that the coating amount of the second catalyst layer slurry is adjusted so that the platinum loading of the second catalyst layer 5 is 0.01 mg / cm 2 .

[0125] The rest of the preparation methods and parameters were the same as those in Example 1.

[0126] Example 7

[0127] The difference between this embodiment and embodiment 1 is that the coating amount of the second catalyst layer slurry is adjusted so that the platinum loading of the second catalyst layer 5 is 0.15 mg / cm 2 .

[0128] The rest of the preparation methods and parameters were the same as those in Example 1.

[0129] Example 8

[0130] The difference between this embodiment and embodiment 1 is that the amount of platinum-carbon catalyst added in the slurry is adjusted so that the platinum loading of the first catalytic layer 4 is equal to the platinum loading of the second catalytic layer 5, both of which are 0.1 mg / cm 2 .

[0131] The rest of the preparation methods and parameters were the same as those in Example 1.

[0132] Example 9

[0133] The difference between this embodiment and embodiment 1 is that by adjusting the drying temperature, the pores of the first catalytic layer 4 are equal to the pores of the second catalytic layer 5, both of which are 35%.

[0134] The rest of the preparation methods and parameters were the same as those in Example 1.

[0135] Example 10

[0136] The difference between this embodiment and embodiment 1 is that the carbon carriers in the platinum-carbon catalysts in the two slurries are the same, so that the specific surface area of ​​the carbon carrier in the first catalytic layer 4 is equal to the specific surface area of ​​the carbon carrier in the second catalytic layer 5, both of which are 900 m 2 / g.

[0137] The rest of the preparation methods and parameters were the same as those in Example 1.

[0138] Embodiment 11

[0139] The difference between this embodiment and embodiment 1 is that the I / C ratio in the first catalytic layer 4 is equal to the I / C ratio in the second catalytic layer 5 by adjusting the content of the ionomer in the second catalytic layer slurry, both of which are 0.9.

[0140] The rest of the preparation methods and parameters were the same as those in Example 1.

[0141] Example 12

[0142] The difference between this embodiment and embodiment 1 is that the I / C ratio in the first catalytic layer 4 is 0.4 by adjusting the content of the ionomer in the first catalytic layer slurry.

[0143] The rest of the preparation methods and parameters were the same as those in Example 1.

[0144] Embodiment 13

[0145] The difference between this embodiment and embodiment 1 is that the I / C ratio in the first catalytic layer 4 is 1.5 by adjusting the content of ionomer in the first catalytic layer slurry.

[0146] The rest of the preparation methods and parameters were the same as those in Example 1.

[0147] Embodiment 14

[0148] The difference between this embodiment and embodiment 1 is that the I / C ratio in the second catalytic layer 5 is 0.05 by adjusting the content of the ionomer in the second catalytic layer slurry.

[0149] The rest of the preparation methods and parameters were the same as those in Example 1.

[0150] Embodiment 15

[0151] The difference between this embodiment and embodiment 1 is that the I / C ratio in the second catalytic layer 5 is 0.8 by adjusting the content of the ionomer in the second catalytic layer slurry.

[0152] The rest of the preparation methods and parameters were the same as those in Example 1.

[0153] Example 16

[0154] The difference between this embodiment and embodiment 1 is that the type of ionomer is adjusted so that the EW value of the ionomer in the first catalytic layer 4 is equal to the EW value of the ionomer in the second catalytic layer 5, both of which are 750 g / eq.

[0155] The rest of the preparation methods and parameters were the same as those in Example 1.

[0156] Comparative Example 1

[0157] The difference between this comparative example and Example 1 is that the platinum-carbon catalyst in the first catalytic layer slurry and the second catalytic layer slurry are of the same type, so that the particle size D50 of platinum in the first catalytic layer 4 is equal to the particle size D50 of platinum in the second catalytic layer 5, both of which are 2 nm.

[0158] The rest of the preparation methods and parameters were the same as those in Example 1.

[0159] Comparative Example 2

[0160] The difference between this comparative example and Example 1 is that the coating order of the first catalytic layer slurry and the second catalytic layer slurry in step (2) is replaced, that is, the second catalytic layer 5 is connected to the proton exchange membrane 3, and the first catalytic layer 4 is connected to the cathode gas diffusion layer 7, so that the particle size D50 of platinum in the catalytic layer close to the proton exchange membrane 3 is 5nm, and the particle size D50 of platinum in the catalytic layer close to the cathode gas diffusion layer 7 is 2nm.

[0161] The rest of the preparation methods and parameters were the same as those in Example 1.

[0162] Performance Testing

[0163] The membrane electrodes prepared in Examples 1-16 and Comparative Examples 1-2 were subjected to polarization performance tests and Pt dissolution durability tests.

[0164] Polarization performance test conditions: DOE_80℃_40 / 40%RH_150 / 150kPaa.

[0165] Durability test conditions: square wave cycle at 0.6-0.95V, one cycle for 6s, a total of 30,000 cycles, temperature 80°C, relative humidity 100%, hydrogen at the anode, nitrogen at the cathode, and normal pressure.

[0166] The above test results are shown in Table 1.

[0167] Table 1

[0168]

[0169]

[0170] Note: Δ refers to voltage increase, ▼ refers to voltage decrease.

[0171] analyze:

[0172] It can be seen from the above table that the membrane electrode designed in the present invention can not only maximize the use of materials and reduce costs, but also take into account the purpose of improving the performance and durability of the membrane electrode, and has good development potential.

[0173] It can be seen from the data results of Example 1 and Examples 4-5 that if the platinum content of the first catalytic layer is too low, the catalyst activity will be reduced, resulting in lower membrane electrode performance; if the platinum content of the first catalytic layer is too high, the catalyst activity will be oversaturated, resulting in no obvious change in membrane electrode performance.

[0174] It can be seen from the data results of Example 1 and Examples 6-7 that if the platinum content of the second catalytic layer is too low, the catalyst activity will be reduced, resulting in lower membrane electrode performance; if the platinum content of the second catalytic layer is too high, the catalyst activity will be oversaturated, resulting in no obvious change in membrane electrode performance.

[0175] It can be seen from the data results of Example 1 and Examples 8-11 and 16 that if the platinum loading of the first catalytic layer is equal to the platinum loading of the second catalytic layer, or the pores of the first catalytic layer are equal to the pores of the second catalytic layer, or the I / C ratio in the first catalytic layer is equal to the I / C ratio in the second catalytic layer, or the EW value of the ionomer in the first catalytic layer is equal to the EW value of the ionomer in the second catalytic layer, the three-phase interface is unevenly distributed, resulting in poor performance and durability.

[0176] It can be seen from the data results of Example 1 and Examples 12-13 that if the I / C in the first catalytic layer is too low, the proton conductivity will decrease, resulting in an increase in the ohmic overpotential and affecting the membrane electrode performance; if the I / C in the first catalytic layer is too high, water flooding is likely to occur, resulting in an increase in the mass transfer overpotential.

[0177] It can be seen from the data results of Example 1 and Examples 14-15 that if the I / C ratio in the second catalytic layer is too low, the proton conductivity will decrease, resulting in an increase in the ohmic overpotential and affecting the membrane electrode performance; if the I / C ratio in the second catalytic layer is too high, water flooding will easily occur, resulting in an increase in the mass transfer overpotential.

[0178] It can be seen from the data results of Example 1 and Comparative Example 1 that if the particle size D50 of platinum in the first catalytic layer is equal to the particle size D50 of platinum in the second catalytic layer, gas mass transfer is affected, resulting in extremely poor performance and durability.

[0179] It can be seen from the data results of Example 1 and Comparative Example 2 that if the particle size D50 of platinum in the first catalytic layer is smaller than the particle size D50 of platinum in the second catalytic layer, the catalyst activity and durability are poor, resulting in reduced performance and stability.

[0180] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A membrane electrode, characterized in that: The membrane electrode comprises a double cathode catalyst layer, a proton exchange membrane and a gas diffusion layer, and the double cathode catalyst layer comprises a first catalyst layer and a second catalyst layer; The first catalytic layer is connected to the proton exchange membrane, and the second catalytic layer is connected to the gas diffusion layer; The raw materials of the dual cathode catalyst layer include a platinum-containing catalyst and an ionomer; The particle size D50 of platinum in the first catalytic layer is less than the particle size D50 of platinum in the second catalytic layer.

2. The membrane electrode according to claim 1, characterized in that: The particle size D50 of platinum in the first catalytic layer is 1-3 nm, preferably 2.2-2.6 nm; Preferably, the particle size D50 of platinum in the second catalytic layer is 4-6 nm, preferably 5.2-5.6 nm; Preferably, the pores of the first catalytic layer are smaller than the pores of the second catalytic layer.

3. The membrane electrode according to claim 1 or 2, characterized in that: The platinum loading of the first catalytic layer is greater than the platinum loading of the second catalytic layer; Preferably, the platinum loading of the first catalytic layer is 0.2-0.3 mg / cm 2 , preferably 0.22-0.26 mg / cm 2 ; Preferably, the platinum loading of the second catalytic layer is 0.05-0.1 mg / cm 2 , preferably 0.06-0.07 mg / cm 2 .

4. The membrane electrode according to any one of claims 1 to 3, characterized in that: The platinum-containing catalyst includes a platinum-carbon catalyst; Preferably, the specific surface area of ​​the carbon carrier in the first catalytic layer is greater than the specific surface area of ​​the carbon carrier in the second catalytic layer; Preferably, the specific surface area of ​​the carbon carrier in the first catalytic layer is 800-1000m 2 / g, preferably 860-900m 2 / g; Preferably, the specific surface area of ​​the carbon carrier in the second catalytic layer is 50-300 m 2 / g, preferably 120-200m 2 / g.

5. The membrane electrode according to claim 4, characterized in that: The ionomer includes any one or a combination of at least two of a fluorinated sulfonic acid polymer, ethanol, water or n-propanol; Preferably, the I / C ratio in the first catalytic layer is greater than the I / C ratio in the second catalytic layer; Preferably, the I / C ratio in the first catalytic layer is 0.6-1.2, preferably 1.1-1.15; Preferably, the I / C ratio in the second catalytic layer is 0.1-0.5, preferably 0.3-0.

4.

6. The membrane electrode according to claim 4 or 5, characterized in that: The EW value of the ionomer in the first catalytic layer is less than the EW value of the ionomer in the second catalytic layer; Preferably, the EW value of the ionomer in the first catalytic layer is 700-800 g / eq, preferably 720-740 g / eq; Preferably, the EW value of the ionomer in the second catalytic layer is 900-1000 g / eq, preferably 905-920 g / eq.

7. A method for preparing a membrane electrode containing a double cathode catalyst layer according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing a platinum-containing catalyst, an ionomer, and a solvent in a first ratio to obtain a first catalyst layer slurry; mixing a platinum-containing catalyst, an ionomer, and a solvent in a second ratio to obtain a second catalyst layer slurry; (2) coating the second catalytic layer slurry on the substrate membrane, and drying it once to obtain the second catalytic layer; coating the first catalytic layer slurry on the second catalytic layer, and drying it twice to obtain the first catalytic layer; (3) placing the side of the substrate membrane covered with the second catalytic layer and the first catalytic layer on one side of a proton exchange membrane, hot pressing, peeling off the substrate membrane to obtain a dual cathode catalytic layer, assembling the dual cathode catalytic layer with a gas diffusion layer to obtain the membrane electrode.

8. The preparation method according to claim 7, characterized in that: In the first mixing step (1), the mass ratio of the platinum-containing catalyst, the ionomer and the solvent is (3-10):(10-20):(30-50); Preferably, in the second proportion mixing of step (1), the mass ratio of the platinum-containing catalyst, the ionomer and the solvent is (1-5):(5-10):(30-40); Preferably, the temperature of the first drying and the second drying in step (2) is independently 60-70°C; Preferably, in step (3), a dielectric membrane is provided on the side of the substrate membrane not covered with the second catalytic layer and the first catalytic layer; Preferably, the material of the base film and the dielectric film is independently any one of polytetrafluoroethylene, polyester resin or polypropylene, or a combination of at least two thereof; Preferably, the temperature of the hot pressing in step (3) is 130-160°C; Preferably, the hot pressing time in step (3) is 30-60s.

9. The preparation method according to claim 7 or 8, characterized in that: The preparation method comprises the following steps: (1) mixing and dispersing a platinum-containing catalyst, an ionomer, and a solvent in a mass ratio of (3-10):(10-20):(30-50) to obtain a first catalyst layer slurry; mixing and dispersing a platinum-containing catalyst, an ionomer, and a solvent in a mass ratio of (1-5):(5-10):(30-40) to obtain a second catalyst layer slurry; (2) coating the second catalytic layer slurry on the substrate membrane, and drying it once at 60-70° C. to obtain the second catalytic layer; coating the first catalytic layer slurry on the second catalytic layer, and drying it twice at 60-70° C. to obtain the first catalytic layer; (3) placing one side of the base membrane covered with the second catalytic layer and the first catalytic layer on one side of a proton exchange membrane, and setting a dielectric membrane on the other side, and then hot pressing at 130-160° C. for 30-60 seconds, peeling off the base membrane to obtain a dual cathode catalytic layer, and assembling the dual cathode catalytic layer with a gas diffusion layer to obtain the membrane electrode.

10. A single battery, characterized in that: The single cell comprises an anode plate, a cathode plate and a membrane electrode as described in any one of claims 1 to 6, wherein the anode plate and the cathode plate are respectively connected to two end surfaces of the membrane electrode.

Citation Information

Cited By

  • Preparation method of platinum-carbon catalyst, catalyst, application and fuel cell membrane electrode

    CN120854586A

  • Preparation method of platinum-carbon catalyst, catalyst, application and fuel cell membrane electrode

    CN120854586B

  • Membrane electrode with multi-layer gradient structure, and preparation method and application of membrane electrode catalyst layer

    CN121460643A